O cuidador profissional de idosos em situação de fragilidade, em ILPI: a relação de cuidado - Mizan, Margherita de Cassia (2018)
Long-lived and fragile old age brings about the need for support in meeting daily needs and instrumental life activities. At present, family ties do not meet these demands and, therefore, adequate places for care such as the ILPIs (Long Stay Institution for the Elderly) are needed, just as the presence of the formal caregiver is fundamental in these institutions. This study was aimed at knowing the meanings and representations that are created in the act of caring for fragile elderly people from the narratives of formal caregivers who work in the care of the elderly and the fragile elderly, that is, what are their profiles, their challenges, and their psychological, social and economic resources. For this purpose, 22 women with employment relationships were interviewed at two institutions and three ILPIs in the city of São Paulo. Those professionals reported the fear of old age, the movement of the families of the elderly at the institutions, the changes in their lives after they became caregivers, the affection that permeates the act of caring, their difficulties in working life, the invisibility of the profession, the fantasies about old age as well as the dependency that exists at this stage of life